A bronchofiberoscopy-associated outbreak of multidrug-resistant Acinetobacter baumannii in an intensive care unit in Beijing, China - Xia Yukun; Lu CuiLing; Zhao Jingya; Han Gaige; Chen Yong; Wang Fang; Yi Bin; Jiang Guoqin; Hu Xiaohua; Du Xianfeng; Wang Zheng; Lei Hong; et al. (BMC Infectious Diseases, 2012)
Abstract Background Bronchofiberscopy, a widely used procedure for the diagnosis of various pulmonary diseases within intensive care units, has a history of association with nosocomial infections. Between September and November 2009, an outbreak caused by multidrug-resistant Acinetobacter baumannii (MDR-Ab) was observed in the intensive care unit of a tertiary care hospital in Beijing, China. This study is aimed to describe the course and control of this outbreak and investigate the related risk factors. Methods Clinical and environmental sampling, genotyping with repetitive extragenic palindromic polymerase chain reaction (REP-PCR), and case–control risk factor analysis were performed in the current study. Results During the epidemic period, 12 patients were infected or colonized with MDR-Ab. Sixteen (72.7%) of twenty-two MDR-Ab isolates from the 12 patients and 22 (84.6%) of 26 MDR-Ab isolates from the bronchofiberscope and the healthcare-associated environment were clustered significantly into a major clone (outbreak MDR-Ab strain) by REP-PCR typing. Seven patients carrying the outbreak MDR-Ab strain were defined as the cases. Six of the seven cases (83%) received bronchofiberscopy versus four of the 19 controls (21%) (odds ratio, 22.5; 95% confidence interval, 2.07–244.84; P = 0.005). Several potential administrative and technical problems existed in bronchofiberscope reprocessing. Conclusions Bronchofiberscopy was associated with this MDR-Ab outbreak. Infection control precautions including appropriate bronchofiberscope reprocessing and environmental decontamination should be strengthened.